2022
DOI: 10.1111/ctr.14620
|View full text |Cite
|
Sign up to set email alerts
|

The heart transplant allocation change attenuates but does not eliminate blood group O waitlist outcome disadvantage

Abstract: Background Patients with blood group O have historically been disadvantaged in the United Network for Organ Sharing (UNOS) heart transplant allocation system. We sought to determine whether the new UNOS allocation system implemented in 2018 had an impact on waitlist and post‐transplant outcomes among blood groups. Methods Using the UNOS database we included all adult patients listed and transplanted with first‐time single‐organ heart transplant between 10/17/15 and 10/1/21. For post‐transplant outcomes, we sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, blood group and PRA status have garnered particular attention as they have significant effect on waitlist times as well as transplant outcomes in some studies. Because of the need for blood group compatibility, patients with blood group O continue to experience longer waitlist times under the current allocation system, 5 with waitlist outcomes potentially improved with durable support, 20 as well as poorer posttransplant outcomes. 21 The findings of the current risk score are in accordance with prior data on the risks associated with blood group O recipients in the current era, which suggests that blood group considerations may be needed to optimize outcomes, as done in the French heart transplant allocation system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, blood group and PRA status have garnered particular attention as they have significant effect on waitlist times as well as transplant outcomes in some studies. Because of the need for blood group compatibility, patients with blood group O continue to experience longer waitlist times under the current allocation system, 5 with waitlist outcomes potentially improved with durable support, 20 as well as poorer posttransplant outcomes. 21 The findings of the current risk score are in accordance with prior data on the risks associated with blood group O recipients in the current era, which suggests that blood group considerations may be needed to optimize outcomes, as done in the French heart transplant allocation system.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In 2018, the United States heart transplant allocation system underwent significant revision, which shifted listing strategies with more patients transplanted with temporary mechanical support (tMCS) and fewer patients transplanted with durable mechanical support (left ventricular assist device [LVAD]). 3,4 The current allocation system resulted in improved waitlist times and increased transplant rates, including for groups who previously experienced particularly prolonged wait times, such as patients with blood group O 5 and elevated body mass index (BMI). 6 Although the current allocation system has maintained similar posttransplant outcomes compared to the prior system, 7 the risk factors for posttransplant mortality under the current allocation system have not been well characterized.…”
mentioning
confidence: 99%
“…Patel et al . [ 19 ], recently, analyzed UNOS data which include 21,565 patients listed for transplantation, and found 14,000 met the criteria to compare the old allocation system with the new one (7035 vs 6965). The found that the new allocation system were associated with changes in O blood group in comparison to in non-O blood group, such as higher transplantation (43.8 vs 51.7) comparison to (63.4 vs 71.6), lower waitlist days (160 vs 33) compression to (77 vs 23) days, and lower waitlist mortality (5.1 vs 3.4) comparison to (4.2 vs 2.5) respectively.…”
Section: Modifying Criteria To Expand Donor Pool For Heart Transplantmentioning
confidence: 99%
“…Although the implemented revisions were designed to group candidates based on objective measures and produce cohorts of patients with similar risk profiles, studies analyzing the policy changes have produced varied results. [3][4][5] For example, the organ procurement and transplantation network (OPTN) thoracic committee analysis in 2019 showed that after 1 year under the new policy, overall patient mortality was highest among status 1 candidates and lowest among status 3, suggesting policy revisions improved patient risk stratification. 6 Other weaknesses of the previous system have not demonstrated improvement under the new policy; waitlist mortality remained stagnant and donor ischemic times significantly increased after the allocation restructuring.…”
Section: Introductionmentioning
confidence: 99%